Modelling of oil water phase inversion in pipeline - Wan Mohamed Irman, Wan Mustapha (2010)
Dispersed oil-water two-phase pipe flow is frequently encountered in the petroleum and chemical processing industry. Conversion between these to types of dispersion is called phase inversion. The types of phase inversion present dependson several parameters such as the volume fraction of the phases, the viscosities of the liquids, the inter-facial tension and the turbulence in the flowing mixture. Predicting the phase inversion experimentally in a two-phase oil-water in pipeline is difficult due to the complexities measurements of the liquid hold-up and pressure drop at high velocities and volume fractions. Hence, a computational fluid dynamic (CFD) simulation using FLUENT 6.3 software was used to understand the flow behaviour. Both water-in-oil and oil-in-water dispersions were possible. In this research oil and water were used as a two-phase flow in pipeline with an internal diameter of 0.024 in and 9.7 in long. Data of the phase distribution profile and liquid hold-up was taken at 7.72 in from the inlet. The k-z model was used to describe the turbulence in continuous phase. The numerical results from the simulation in terms of the phase distribution profiles and average in-situ hold-up are compared with experimental results by Soleimani (1999). Results that are presented and discussed shows acceptable agreement with the experimental data compared. From this work, it does appear that CFD simulation technique can be successfully applied for the numerical simulation of liquid-liquid dispersed flow.